Happiness versus happycracy - Latorre Ariño, Marino (2019)
This article reflects on the concept of happiness throughout history, and its relationship with the three reference points of classical philosophy: the truth, the goodness and the beauty. It discusses whether the digital technologies are leading us to or move us away from happiness. The article tries to give an answer to questions such as, can we educate to develop a happy life? What is the influence of education to reach happiness? Can the effort and the well-done work be a source of happiness? The article deals also, in a critical manner, with the concept of happycracy and its meaning in relation to Positive Psychology, as well as the ideology and the different types of interest that underlie many current proposals to achieve a happy life.